The Convergence of Percapita Income in Central Sulawesi Province: Konvergensi Pendapatan Perkapita di Provinsi Sulawesi Tengah - Nurjanna Ladjin; Burhanudin Ladjin; Arianto Taliding (Jurnal Sinar Manajemen, 2023)
This research aims at analyzing the influence of economic growth and human development index on the poverty rate of 13 regencies/cities in Central Sulawesi Province. The data were analyzed using panel data which employed Eviews version 11 software. The result of fixed effect model regression shows that economic growth and mean years of schooling negatively and significantly affect poverty rate, life expectancy and per capita expenditure positively and significantly affect poverty rate, and expected years of schooling does not affect poverty rate in regencies/cities of Central Sulawesi Province. To mitigate the poverty rate constant reference to pro-poor, pro-job, and pro-growth policies should be maintained and job vacancy need to be expanded and regency/city government could increase the realization of school and teacher facility spending budget allocation, administer nonformal education which can increase workers’ productivity, provide hospital, public health center, secondary public health center and health personnel facilities, public infrastructure and education assistance such as providing training on creativity in cooperatives and micro-, small-, and medium-enterprises (MSMEs).